Synthesis of sparse rectangular planar arrays with weight function and improved grey wolf optimization algorithm - Tao, Kui; Wang, Bin; Tian, Xue; Tang, Qi; Xie, Guihan (IET microwaves, antennas & propagation, 2024)
The present article proposes a novel hybrid approach for addressing the synthesis problem of rectangular planar arrays under multiple constraints, through joint optimization of the weight function and the improved grey wolf optimization (IGWO) algorithm. Firstly, the grey wolf optimization (GWO) algorithm is improved by using tent chaotic mapping, nonlinear convergence factor, dominant wolf dynamic belief strategy, and opposition‐based learning strategy to increase the population diversity and the ability to jump out of the local optimum. Secondly, the array elements are weighted using the weight function to generate the position distribution matrix, which reduces the thinned matrix optimization time and improves the optimization efficiency. Finally, the position distribution matrix is used to generate the thinned array, and the IGWO algorithm is applied to perform the sparse optimization with multiple constraints. The effectiveness of the method is verified through numerical simulation and full‐wave simulation experiments, demonstrating its capability to enhance array antenna performance and reduce peak sidelobe level (PSLL). These experimental results hold significant engineering implications and provide valuable references for addressing the array distribution problem under multiple constraints. In this article, a novel hybrid method is proposed to solve the synthesis problem of rectangular planar arrays under multiple constraints. The ability of the proposed method in enhancing the array antenna performance and reducing the peak side lobe level (PSLL) is demonstrated through numerical simulations and full‐wave simulation experiments.